Changes in Physicochemical Properties and In Vitro Digestibility of Broken Rice Starch by Ultrasound and Quercetin Dual Treatment - Ping Yang; Chenhao Qiu; Na Zhang (Applied Sciences)
Applying physical modification methods to raise the resistant starch content is a feasible strategy for developing foods with a low glycemic index (GI) and regulating postprandial hyperglycemia. Here, broken rice starch (C) was modified via ultrasound and quercetin complexation (US-Q). The structure, physicochemical properties, and in vitro digestibility of the US-Q product were subsequently determined. Scanning electron microscopy (SEM) images showed that the modification changed the starch granules’ morphology, forming a more compact and stable structure. Fourier transform infrared (FTIR) spectroscopy images revealed the interaction between the starch and quercetin. An X-ray diffraction (XRD) analysis demonstrated that the crystallinity of the US-Q was lower than that of the C, indicating that the combined modification with ultrasound and quercetin disrupted the long-range ordered structure of the starch and facilitated the formation of a short-range ordered structure from amylose. Size exclusion chromatography (SEC) images showed that both the molecular weight (from 72,080.96 kDa to 85,141.95 kDa) and amylose content (from 15.94% to 26.76%) increased significantly, while the branching degree and average degree of polymerization of amylopectin decreased, suggesting that the ultrasonic treatment processing method had a significant impact on the formation of the quercetin–starch complexes. In terms of in vitro digestion, the resistant starch content of the US-Q was significantly increased from 6.57% to 20.23%, whereas the hydrolysis rate was decreased from 92.6% to 78.35%, indicating that the presence of quercetin reduced the digestibility of the starch complexes by inhibiting the starch-hydrolyzing enzyme activity. Overall, this study improves the understanding of ultrasound and quercetin dual treatment of broken rice starch, providing a theoretical basis for the development of low-GI starch foods for industrial applications.